Assessment of Noninvasive Regional Brain Oximetry in Posterior Reversible Encephalopathy Syndrome and Reversible Cerebral Vasoconstriction Syndrome. (July 2016) - Chung, David Y.; Claassen, Jan; Agarwal, Sachin; Schmidt, J. Michael; Mayer, Stephan A.
Background: Posterior reversible encephalopathy syndrome (PRES) leads to small- and large-vessel circulatory dysfunction. While aggressive lowering of elevated blood pressure is the usual treatment for PRES, excessive blood pressure reduction may lead to ischemia or infarction, particularly when PRES is accompanied by reversible cerebral vasoconstriction syndrome (RCVS). Regional cerebral oximetry using near-infrared spectroscopy is a noninvasive modality that is commonly used intraoperatively and in intensive care settings to monitor regional cerebral oxygenation (rSO2 ) and may be useful in guiding treatment in select cases of PRES and RCVS. Results: We report a case of a patient with PRES complicated by infarction and RCVS where the optimal blood pressure management was unclear. A decision was made to decrease blood pressure which resulted in an improved neurological examination and increase in rSO2 from 40% to 55% in at-risk brain. Infarcted brain as determined by diffusion-weighted magnetic resonance imaging and computed tomography perfusion imaging showed no change in rSO2 during the same time period. Furthermore, there was a qualitative change in the rSO2 –mean arterial pressure (MAP) relationship, suggesting an alteration in cerebrovascular autoregulation as a result of lowering blood pressure. Conclusions: Regional cerebral oximetry can provide valuable diagnostic feedback in complicated cases of PRES and RCVS.